Investigation of planer laser induced fluorescence as an instantaneous field measuring technique in water - Alrifaai, Hatim Hamid (Kansas State University, 2023)
This dissertation aims to study the use of the Planar Laser Induced Fluorescence (PLIF) technique to measure the instantaneous temperature field of water flowing through a duct. An experimental facility was developed specifically for PLIF visualization in water flow. In the duct, the bottom side is changeable and heated by an electrical heater. Rhodamine B and Nd: YAG laser (532 nm) were used to create the fluorescence in the experiment. The study presents techniques for making a temperature calibration curve. In addition, the research seeks to determine the best experimental conditions to enhance the accuracy and precision of the results. The primary focus of the study was the application of these techniques to determine an instantaneous field temperature in the flowing water duct. Several experimental factors were investigated to find their impact on the results’ accuracy and precision. The temperature field and temperature distribution curve were measured for the isothermal and heating cases. Smooth and finned surfaces were examined. The investigation focused on the area close to the bottom surface of the duct. The experimental results were compared with computational results obtained by the FLUENT software. The study concluded that PLIF can be used for instantaneous field, but that high temperature gradients confound the usefulness of the results.
Keywords: Temperature field; Planar laser induced fluorescence; PLIF